PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI, DAN SISTEM PENGUKURAN KINERJA TERHADAP KINERJA MANAJERIAL PADA BUMN DI KOTA BANDA ACEH - Adiyatma, M. Farhan; Saleh, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims (1) to examine the effect of budgeting on managerial performance, (2) to examine the effect of organizational commitment on managerial performance, (3) to examine the effect of measuring managerial performance, (4) to examine budgetary participation, organizational commitment, and the system. simultaneous measurement of performance on managerial performance. The population in this study were state-owned companies in Banda Aceh City, which amounted to 19 companies. The respondents are Top Managers and Middle Level Managers who are responsible for the preparation of the budget and finances of each BUMN so that the respondents found 38 managers. This study uses the census method where the entire population is used as the object of research. The analytical method used is multiple linear regression with SPSS version 25 application. The results of the study prove that budget participation and performance measurement have a significant positive effect on managerial performance. Organizational commitment has no effect on managerial performance.